Children Learning in Science Model Integrated with Project-Based Worksheets on Students' Science Process Skills - Alam, Rahim; Israwaty, Ila; Krismanto, Wawan (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The research aims to determine the effect of the Children Learning In Science (CLIS) model integrated with project-based worksheets on students' Science Process Skills (SPS). The approach in this study is a quantitative with a quasi-experimental research type using the Post-test Only Control Group Design. The population is fifth-grade students of SDN 3 Parepare, and the sample used in this study were all students in class V.1 as an experimental class and class V.3 as a control class. Data were obtained by an essay SPS test. The data analysis used was the Independent Sample T-test. The results showed that in the experimental class, in addition to being guided by project-based worksheets, each learning syntax has directed students to carry out project completion procedures using their SPS, such as observing, concluding, classifying, making predictions, and communicating the results. Based on the inferential statistical analysis with the T-Test, it produces a Sig value (2tailed) = 0.000 <0.05. Therefore, H0 is rejected, and H1 is accepted. Thus, there is a difference in SPS in the control and experimental classes. The conclusion is that there is an influence of the CLIS learning model of project-based worksheets on students' SPS.